2021
DOI: 10.1002/adhm.202170056
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Drug Delivery: Zn‐MOF Encapsulated Antibacterial and Degradable Microneedles Array for Promoting Wound Healing (Adv. Healthcare Mater. 12/2021)

Abstract: In article number 2100056 by Yongan Wang, Yuan Luo, Yuanjin Zhao, and co‐workers, a ZIF‐8@MeHA microneedle (MN) array is fabricated by template molding method for wound healing. Such an MN patch has a good antibacterial effect by releasing Zn2+ to kill microbes. Meanwhile, the MeHA hydrogel is capable of promoting the regeneration of neonatal epithelial tissues through gradual degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 0 publications
0
43
1
Order By: Relevance
“…The mechanical strength of the MNs was measured to be 0.9 N per needle when the displacement was 0.2 mm. Compared with previous reports, 35 the MNs had sufficient mechanical strength. To explore the penetration depth of the tips, MNs were puncturing into isolated rat skin.…”
Section: Mechanical Strength and Insertion Capability Of The Mnscontrasting
confidence: 59%
See 1 more Smart Citation
“…The mechanical strength of the MNs was measured to be 0.9 N per needle when the displacement was 0.2 mm. Compared with previous reports, 35 the MNs had sufficient mechanical strength. To explore the penetration depth of the tips, MNs were puncturing into isolated rat skin.…”
Section: Mechanical Strength and Insertion Capability Of The Mnscontrasting
confidence: 59%
“…[24][25][26][27][28][29][30][31] Since the contact area between the MNs and the wound is greatly increased, MNs loaded with active drugs have also been used to promote wound healing and have a significant therapeutic effect. [32][33][34][35] Based on these merits, MNs are considered a robust drug delivery system for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] The metal ions and the rough surface of these crystals, which can increase the contact area between MOFs and tissues, have been considered to enhance the biological effect of MOFs. [ 38 ] On the basis of the previous research, zinc and copper ions were the regenerative factors for the tendon‐to‐bone interface repair . [ 39 ] In this study, due to exceptional thermal and chemical resistance to water and organic solvents, the ZIF‐11 was selected as the regenerative factor rather than other ZIFs, which should be mixed in the organic solvent (hexafluoroisopropanol) during the electrospun fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…However, the toxin concentration detected by the NIH‐3T3 cytotoxicity assay is within 72 h, making it difficult to extrapolate the results to scenarios, where other, less‐sensitive tests are used. [ 29 ] Another previous study demonstrated that ZIF‐8 shows no significant cytotoxicity in various cell lines up to a threshold value of 30 µg mL −1 , showing cytotoxicity at higher concentrations. [ 30 ] Regarding the mechanism, cytotoxicity results from the effects of released Zn 2+ on mitochondrial production of reactive oxygen species and may cause irreversible DNA damage, ultimately initiating cellular apoptosis pathways.…”
Section: Resultsmentioning
confidence: 99%